Remediation of arsenic and persistent organic contaminants using enhanced in-situ methods - Sullivan, Mary Elizabeth, author; Carlson, Kenneth, advisor; Pruden, Amy, advisor (Colorado State University. Libraries, 2008)
The demand for inexpensive and reliable water treatment technologies continues to increase as the number of contaminants grows and their associated fate and transport mechanisms become more complex. Advances in public health have contributed to the implementation of more stringent drinking water standards for compounds such as arsenic. Furthermore, advances in analytical chemistry have contributed to the detection of previously immeasurable compounds including endocrine-disrupting compounds (EDCs), pharmaceuticals and personal care products (PPCPs), and other bioactive chemicals in wastewater effluents and surface waters around the world. This research examined the use of enhanced in-situ methods for the remediation of arsenic and several persistent organic contaminants. Unamended and amended electrokinetic remediation (ER) column studies conducted to determine the impact on arsenic revealed arsenic removal from the soil column due to the electrolysis of water and electromigration of the charged species. Column studies also examined the impact of amended aquifer recharge and recovery (ARR) treatment on persistent organic compounds. Water treatment residual-amended ARR columns were utilized to promote an environment capable of reducing flame retardants. The results indicated that the presence of water treatment residuals created a reducing environment and provided ideal adsorption sites and sources of organic matter in the form of leached carbon. Unamended and amended ER column studies were completed to examine the impact on two pharmaceuticals (sulfamethoxazole and carbamazepine) and three organophosphorus flame retardants (tris-(2-chloroethyl) phosphate, tris-(2-chloro-, 1-methylethyl)phosphate, and tris-(2-chloro-, 1-chloromethyl-ethylphophate). Results indicated that the highest removal results occurred in the significant redox zones of the ER column. Oxidizing conditions at the anode and reducing conditions at the cathode had significant impacts on the compounds' concentrations in the column's pore water. Lastly, critical characterization of the compounds' affinity for aqueous, colloidal, and solid phases was determined for the five organic compounds. These results, as well as sources of flame retardant contamination in the experimental design, was useful (and necessary) in interpreting the treatment results from the amended ARR and electrokinetic column studies.
Keywords: aquifer recharge-recovery; arsenic; electrokinetic remediation; persistent organic contaminants; environmental science; environmental engineering